Pengaruh Personal Selling terhadap Minat Beli Produk PRUlink Generasi Baru Nasabah Prudential Life Assurance Indonesia - Nico Aprianto; Diah Ayu Candraningrum (Prologia, 2019)
This study aims to examine how strong the influence of Personal Selling on Interest in Purchasing New Generation PRUlink products for Prudential Life Assurance Indonesia customers. The data of this study were obtained from the results of questionnaires of 153 Prudential Life Assurance Indonesia customers regarding interest in purchasing New Generation PRUlink products. In this study the research method used is quantitative which aims to test the instrument using the validity, reliability and normality test. The results of data processing using SPSS states that the variable Personal selling (X) influences significantly to the variable purchase interest (Y). Correlation coefficient test results explained there will be a strong relationship between Personal selling (X) to the variable buying interest (Y). Meanwhile, the dimensions that support the effectiveness of personal selling include ability approaching, presentation, handling objection, and closing. The ability to start communication, presenting products, being able to answer prospective customer questions, and close communication well, be an attraction for prospective customers to be the customer. Penelitian ini bertujuan untuk meneliti seberapa kuat pengaruh Personal Selling terhadap Minat Beli produk PRUlink Generasi Baru nasabah Prudential Life Assurance Indonesia. Data penelitian  diperoleh melalui penyebaran kuesioner terhadap 153 nasabah Prudential Life Assurance Indonesia mengenai minat beli produk PRUlink Generasi Baru. Penelitian ini merupakan penelitian kuantitatif menggunakan metode survei. Pengujian instrumen berupa uji Validitas, Reliabilitas dan Normalitas. Pengolahan data menggunakan Statistical Package for Social Sciences (SPSS) dan memperoleh hasil bahwa variabel Personal selling (X) berpengaruh secara signifikan terhadap variabel Minat beli (Y). Hasil uji koefisien korelasi menjelaskan akan adanya hubungan yang kuat antara Personal selling (X) terhadap variabel Minat beli (Y). Adapun, dimensi yang mendukung efektivitas personal selling meliputi kemampuan pendekatan, presentasi, mengatasi keberatan, dan penutupan. Kemampuan dalam membuka komunikasi, mempresentasikan produk, mampu menjawab pertanyaan calon nasabah, dan menutup komunikasi dengan baik, sehingga mampu menarik calon nasabah membeli produk asuransi.